Cardiopulmonary physiology and responses of ultramarathon athletes to prolonged exercise - Blaber, A. P.; Walsh, M. L.; Carter, J. B.; Seedhouse, E. L.; Walker, V. E. (Canadian Journal of Applied Physiology, 2004)
The purpose of this study was to determine the changes of pulmonary function and autonomic cardiovascular control after an ultramarathon and their relation to performance. Eight entrants to the Canadian National Championship 100-km running race participated in the study. Pulmonary function and 30-s maximum voluntary ventilation (MVV30s) tests were conducted one day before the race and within 5 minutes of race completion. Heart rate and blood pressure data were collected 30 min before and 5 min after the race as well as during a 10-min stand test one day prior to the race. During the race, beat-by-beat R-R interval data were collected over the first and last 20 km. The results showed that MVV30s and MVV30s tidal volumes were reduced postrace (p < 0.001). Prerace supine total harmonic variation (p < 0.01) and prerace MVV values (10 s to 30 s) (p < 0.05) were correlated with race finish time. The changes in pulmonary function and MVV30s values from pre- and postrace were not significantly correlated to race performance. We conclude that maximal sustainable ventilatory power and dynamic autonomic cardiovascular control are important factors in determining overall performance in an ultramarathon.